Inhibiting Factors of Non Governmental Organizations in the Education Cluster Policy Network for the Implementation of a Child Friendly City in Padang City - Kurniawan, Wahyu Shandi; Malau, Hasbullah (The Future of Education Journal, 2025)
This study aims to identify the inhibiting factors faced by non-governmental organizations within the education cluster policy network in the implementation of a Child-Friendly City in Padang City. This research employs a qualitative method with a descriptive approach conducted in Padang City, West Sumatra Province. Data were collected through interviews, observations, and document studies, and the validity of the data was verified using source triangulation techniques. The findings indicate that several factors hinder the policy network's engagement with non-governmental organizations in the education cluster, including limited program funding, ineffective and suboptimal communication among actors within the network, and a lack of training and resources for the programs implemented by non-governmental organizations.